Antiplasmodial Property of Glycyrrhiza glabra Traditionally Used for Malaria in Iran: Promising Activity with High Selectivity Index for Malaria - Ali Ramazani; Mahdi Tavakolizadeh; Samira Ramazani; Hamidreza Kheiri-Manjili; Mehdi Eskandari (Journal of Arthropod-Borne Diseases, 2018)
Background: Development of resistance against the frontline anti-malarial drugs has created an alarming situation, which requires intensive drug discovery to develop new, more effective, affordable and accessible anti-malarial agents. The aim of this study was to assess antiplasmodial activity of the different fractions of root extract of Glycyrrhiza glabra. Methods: Roots of G. glabra were collected from Tarom district of Zanjan Province in 2016 and then dried root material was chopped and consecutively extracted by the percolation method using solvents of different polarity. Resulting extracts were assessed for in vitro and in vivo anti-malarial and cell cytotoxicity activities. Results: Among the three different solvent fractions studied, water-methanol and ethyl acetate fractions showed promising in vitro antiplasmodial activity against CQ-sensitive Plasmodium falciparum 3D7 strain (IC50= 9.95 and 13µg/ml, respectively). Further, the selectivity indices (HeLa cells versus P. falciparum) for the promising water-methanol fraction showed selectivity for P. falciparum and potential safer therapy for human. Interestingly, water-methanol and ethyl acetate fractions showed a significant suppression of parasite growth (72.2% and 65%, respectively) in comparison with control group in mice infected with P. berghei (P< 0.05). Conclusion: The promising antiplasmodial activity of the aqueous fraction of G. glabra obtained in our study warrant bioassay-guided fractionation of this fraction to identify active principles responsible for antiplasmodial activity.